Gestión pedagógica durante educación en emergencia (COVID-19), Circuito Educativo Intercultural Bilingüe 06D01C17_b, Riobamba, abril – junio 2020. - Hernández Zumba, Inés María (2022)
Abstrac The research is based on the analysis of the pedagogical management developed by teachers and academic performance during education in the COVID-19 emergency in different educational, economic and social contexts in the Bilingual Intercultural Educational Circuit 06D01C17_b, Riobamba, April - June 2020 and students' perception of it. In this evaluation, the quality of the implemented strategies was established, the strength of the teachers' accompaniment in the educational process, the importance of the involvement of the family in school activities and the perception of the students of the elementary, middle, higher and higher levels. high school. In this context, the objective of the research was to propose post-COVID-19 pedagogical strategies that aim to improve the socio-emotional and academic fields in an interdisciplinary way. Methodologically, we worked with a qualitative approach, of a non-experimental design; descriptive level, by place, field and bibliographic; by time, transversal; by the research method: descriptive and analytical. In the development of the research, the survey with the survey sheet instrument was used as techniques; interview with the application of the questionnaire. The population was made up of students and teachers of the 06D01C17_b Intercultural Bilingual circuit, while the sample was probabilistic and consisted of 162 students. The proposal is structured by pedagogical strategies that strengthen the communicational, emotional and cognitive field of students in the educational levels of basic elementary, middle, higher and high school, thus pointing to the problem investigated. Keywords: Pedagogical management - Education in emergency - Learning.